Teacher–child relational conflict in Head Start – exploring the roles of child behaviour, teacher stress, and bias, and classroom environment. Issue 8 (10th June 2020) - Chen, Shiyi; Phillips, Beth; Izci, Burcu
ABSTRACT: Numerous studies have examined influential factors on teacher–child relational conflict; however, only a limited number of studies have presented in-depth portrayals of teachers' conflict with children living in poverty at the preschool level. The purpose of this paper is to explore teacher, child, and contextual characteristics that influence teacher–child relational conflict in Head Start. Ten Head Start teachers from five centres across two counties were recruited. Each participant was interviewed twice and observed once for an entire school day. Interview and observation data were analysed through a grounded theory approach by using the qualitative data analysis software NVivo. Four themes emerged as teacher-perceived influences on conflictual relationships: children's behaviour, teachers' stress and biases, and the classroom environment. The results may have implications for teacher professional development and Head Start policies.